A Comparative Study of Grade 8 Science Students’ Academic Achievement under Teacher-Centered Learning Method and Inquiry-Based Learning Method at the Demonstration School of Ramkhamhaeng University in Bangkok, Thailand - Mohammadi, Negar; Lynch, Richard (Scholar: Human Sciences, 2021)
The purpose of this study was to compare students’ academic achievement under two different teaching methods which were teacher-centered learning method and inquiry-based learning method. Two groups of Grade 8 students of The Demonstration School of Ramkhamhaeng University (DSRU), Bangkok, Thailand comprised the sample for this research. The study was conducted over a period of seven weeks from February 2019 to April 2019. The science achievement scores were analyzed by means, standard deviations, a paired sample t-test and an independent samples t-test (one-tailed). The findings of the study did not show a significant difference between teacher-centered learning method and inquiry-based learning method. Recommendations have been suggested for the school, teachers, students and future researchers.